1983
DOI: 10.1016/0014-5793(83)80417-7
|View full text |Cite
|
Sign up to set email alerts
|

Neurotensin modulates human neutrophil locomotion and phagocytic capability

Abstract: Neurotensin (NT) was found to induce oriented locomotion and augment the phagocytic capability of human blood neutrophils over lo-"-lo-' M. The tridecapeptide also causes Ca2* extrusion from neutrophils, very likely as a result of intracellular Ca2+ mobilization. It is suggested that the NT-mediated functional modulation of neutrophils correlates with the capacity of NT to affect the i'~tracellular compartmentalization of Ca 2+ . Peripheral NT-elicited phenomena such as vasodilation, enhanced vascular permeabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
2

Year Published

1986
1986
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 24 publications
0
21
0
2
Order By: Relevance
“…It is likely that the COX-2-independent increase in proliferative capacity demonstrated by NMCM-cultured intestinal epithelial cells is related to 'conditioning' of medium with mitogenic factors by non-activated RAW264.7 macrophages (Rosenberger et al, 2000). This phenomenon has been described in models using a variety of target cells (Goldman and Bar-Shavit, 1979;Hauptmann et al, 1993). In keeping with our observations that macrophage COX-2 activity promotes intestinal epithelial cell proliferation in vitro, Sonoshita et al (2001) have recently reported that stromal cell COX-2 drives increased epithelial cell proliferation in Apc D716 mouse adenomas.…”
Section: Discussionmentioning
confidence: 98%
“…It is likely that the COX-2-independent increase in proliferative capacity demonstrated by NMCM-cultured intestinal epithelial cells is related to 'conditioning' of medium with mitogenic factors by non-activated RAW264.7 macrophages (Rosenberger et al, 2000). This phenomenon has been described in models using a variety of target cells (Goldman and Bar-Shavit, 1979;Hauptmann et al, 1993). In keeping with our observations that macrophage COX-2 activity promotes intestinal epithelial cell proliferation in vitro, Sonoshita et al (2001) have recently reported that stromal cell COX-2 drives increased epithelial cell proliferation in Apc D716 mouse adenomas.…”
Section: Discussionmentioning
confidence: 98%
“…NT regulates several biological processes, such as intestinal motility, secretion, vascular smooth muscle activity, and intestinal epithelial cell proliferation, but recent evidence indicates that in NT there is also a potent neuroimmunomodulator (43). Thus NT interacts with leukocytes, mast cells, and macrophages, inducing cytokine release and enhancing chemotaxis (14,16,21). Recent in vivo evidence supports the view that NT may be involved in acute and chronic inflammatory disorders.…”
mentioning
confidence: 90%
“…NT also interacts in vitro with immune and inflammatory cells, including leukocytes (10), peritoneal mast cells (7), and macrophages (11,12). Although these studies point to a role for NT in inflammatory reactions, the possibility that this peptide participates in the pathogenesis of colonic inflammation has not been examined.…”
Section: Introductionmentioning
confidence: 99%